PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP MOTIVASI KUNJUNGAN WISATA KE PULAU SIRANDAH PADANG - Aprinal Eko Saputra; Rini Eka Sari (Politeknik Negeri Padang, 2018)
Instagram as one of social media, has significant inluence toward the tourisst visit to a tourism destination. This study aimed to find out the form and the amont of Instagram social media effect toward tourists visit to Sirandah island, Padang. The data analysis method used in this research is descriptive quantitative. Primary data were obtained by speading questioners while other supporting data collected by observation, literature study, and documentation. The result shows that Instagram social media affects positively toward the tourists visit to Sirandah Island. The amount of its effects is 35 % while the other 65 % is influenced by other variable outside the scope of this research.